Conselho nacional de justiça e transconstitucionalismo latino-americano: uma atuação densificadora do sistema de proteção dos direitos humanos - Oliveira, Gisele Souza de (2024)
The National Council of Justice (CNJ) was created by Constitutional Amendment 45/2004 with the mission of controlling the administrative and financial activities of the Judiciary and ensuring compliance with the functional duties of the judiciary. In its journey of self-affirmation and institutional maturation, the body has faced challenges that have revealed new potential for action. Going beyond its initial vocation, but in line with constitutional dictates, the CNJ has taken on other relevant roles, articulating the construction of solutions to some scenarios of serious human rights violations in Brazil. With this in mind, the purpose of this study is to research the work of the CNJ in the context of what is known as Latin American transconstitutionalism, through an analysis that uses the theoretical lenses of transconstitutionalism, a construct formulated by Professor Marcelo Neves. The aim is to answer the following research problem: to what extent is the CNJ's action in the field of human rights defense and protection in line with the premises of so-called Latin American transconstitutionalism, so as to contribute to updating the programming of the domestic legal order in the light of the influences of the Inter-American Human Rights System (IACHR)? What's more, has this action contributed to the densification of the human rights protection system in Brazil? We start from the hypothesis that the CNJ has stood out as a differential actor in the field of Latin American transconstitutionalism by stimulating, through a set of concrete actions, that the Brazilian legal order observes, with the necessary reflexivity, the order of the ISHR, an action that has undeniably contributed to the densification of the protection of human rights. To this end, in the first chapter, we set out the current context of constitutionalism in world society, focusing on the overcoming of the state paradigm, in order to introduce the basic theory. In the second, we outline the history of human rights, their foundations and perspectives, the protection systems, with an emphasis on the ISHR, and we define Latin American transconstitutionalism as a dialogue between the orders of national states and the ISHR, with a willingness to learn from each other bilaterally, triangularly or multiannually. On the third level, we trace the trajectory of the reform of the Judiciary that culminated in the creation of the CNJ, addressing the process of self-affirmation and institutional maturation. By 10 systematizing the work of the CNJ, we classified it into four types (normative function, promotion function, monitoring function and institutional coordination function) and concluded that it is in line with the premises of transconstitutionalism and that it has promoted the densification of the protection of human and fundamental rights. To prepare the text, we used the bibliographical research technique and adopted the deductive method, starting from the principles and premises of the theory of transconstitutionalism (major premise) and then analyzing the CNJ's actions (minor premise), drawing the conclusion that, in this way, the CNJ acted in line with the premises of the basic theory, since it promoted intertwining between legal orders, in a heterarchical way and with the possibility of reciprocal learning